Disease free seed production of wheat in Punjab: Achievements - Sharma, R C; Sharma, I; Kaur, Daman Jeet; Bala, Ritu (Journal of Cereal Research, 2011)
Punjab Agricultural University (PAU), Ludhiana produces and supplies about 3,000 tonnes of wheat seed (nucleus/ breeder/foundation/certified/TL), annually, to various public and private seed production agencies including farmers. Up to 1990s, the wheat continued to suffer heavy qualitative and quantitative losses due to severe incidence of seed borne diseases viz., loose smut (Ustilago segetum var. tritici), Karnal bunt (Tilletia indica) and ear cockle nematode (Anguina tritici). Keeping in view the destructive nature, these diseases were designated as objectionable under the Indian Seed Act, 1968 and minimum tolerance levels were fixed for them in foundation and certified seed. The present study highlights the impact of various management strategies on the status of these diseases in Punjab vis-Ã -vis seed health. Nearly complete control of loose smut and ear cockle nematode has been achieved at seed production farms and farmerâ€™s fields through chemical and mechanical seed treatments and seed replacement through introduction of new varieties and organization of farmerâ€™s awareness and participatory programmes. Carboxin, carbendazim and triazole compounds have proved highly effective against loose smut. The nematode galls are easily separated by the seed processing machines or floating on brine solution. However, in the past, Karnal bunt has been an elusive problem where complete control could not be achieved. Nevertheless, a single foliar spray of propiconazole or tebuconazole or hexaconazole at heading stage provided a considerable control of the disease in seed plots. The concerted efforts have resulted into the identification of resistant stocks against Karnal bunt are being used for incorporating resistance in high yielding wheat which will probably be a long lasting solution for this problem.